Tumor-Derived Exosomal Non-Coding RNAs: The Emerging Mechanisms and Potential Clinical Applications in Breast Cancer - Yi, Yi; Wu, Min; Zeng, Hong; Hu, Weijie; Zhao, Chongru; Xiong, Mingchen; Lv, Wenchang; Deng, Pei; Zhang, Qi; Wu, Yiping (Frontiers in Oncology, 2021)
Breast cancer (BC) is the most frequent malignancy and is ranking the leading cause of cancer-related death among women worldwide. At present, BC is still an intricate challenge confronted with high invasion, metastasis, drug resistance, and recurrence rate. Exosomes are membrane-enclosed extracellular vesicles with the lipid bilayer and recently have been confirmed as significant mediators of tumor cells to communicate with surrounding cells in the tumor microenvironment. As very important orchestrators, non-coding RNAs (ncRNAs) are aberrantly expressed and participate in regulating gene expression in multiple human cancers, while the most reported ncRNAs within exosomes in BC are microRNAs (miRNAs), long-noncoding RNAs (lncRNAs), and circular RNAs (circRNAs). Notably, ncRNAs containing exosomes are novel frontiers to shape malignant behaviors in recipient BC cells such as angiogenesis, immunoregulation, proliferation, and migration. It means that tumor-derived ncRNAs-containing exosomes are pluripotent carriers with intriguing and elaborate roles in BC progression via complex mechanisms. The ncRNAs in exosome are usually excavated based on specific de-regulated expression verified by RNA sequencing, bioinformatic analyses, and PCR experiments. Here, this article will elucidate the recent existing research on the functions and mechanisms of tumor-derived exosomal miRNA, lncRNA, circRNA in BC, especially in BC cell proliferation, metastasis, immunoregulation, and drug resistance. Moreover, these tumor-derived exosomal ncRNAs existed in blood samples are proved to be excellent diagnostic biomarkers for improving diagnosis and prognosis. The in-depth understanding of tumor-derived exosomal ncRNAs in BC will provide further insights for elucidating the BC oncogenesis and progress and exploring novel therapeutic strategies of combating BC.